Overcoming Challenges in Recruitment of South Asians for Health Disparities Research in the USA - Mukherjea, Arnab; Ivey, Susan L.; Shariff-Marco, Salma; Kapoor, Nilesh; Allen, Laura (Journal of racial and ethnic health disparities, 2018)
South Asians—individuals with origins in the countries of Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, Sri Lanka, and other regions of the subcontinent—are an understudied and at-risk racial/ethnic minority population for disproportionate burden of preventable diseases in the USA. Notwithstanding lack of research disaggregating Asian American subgroups, a key factor in this paucity of data is the lack of participation and engagement of community members in studies which examine distribution and determinants of adverse health outcomes. The purpose of this case study series is to elucidate distinct barriers in recruitment of South Asians in health disparities research within four diverse study designs. These illustrations are followed by a discussion of effective strategies and promising practices to increase and enhance the participation of community members in health-related studies in order to ultimately understand and address disparities among this rapidly growing cultural group in the US systematic collection of data which not only is representative of this understudied population but also elucidates contextual influences on community health and wellbeing and is pivotal to the reduction and elimination of preventable disparities among South Asians in the USA.